Pendidikan Anti Korupsi di SMA Kabupaten Pacitan - Mukodi Mukodi (Jurnal Penelitian Pendidikan, 2013)
Rampant corruption occurred recently is essentially a portrait of the accumulated actions of society in carrying out the activities of daily life. Itmust be recognized that educational institutions , especially the world of schooling also donates seeds of the corruptive behaviour, manipulative andnepotism in a certain level, primarily in the transfer of knowledge and the transfer of value to the learning process in the classroom cubicles, and schools.The process of awareness against the corruption must be inculcated and struggled for its existence in order that Indonesia will be free from the bondage ofthe corruption crime soon. Anti- corruption education in high school Pacitan is an alternative solution- to unravel the "culture" of the corruptionprevailing in all life lines of the Indonesian people.The research reveals that students ' and teachers' understanding of the corruption is high. It is proved from the 339 respondents, 90.6 % claim tounderstand and very aware that corruption is a despicable act and against the law. Only 9.4 % do not understand that the corruption includes a criminalbehaviour. Meanwhile, a motivation of society to learn the eradication of the corruption is very high, namely 85.3 % of the 252 available respondents,only 14.7 % of them who are not motivated. The awareness of learning the crime and the negative effect of the corruption is quite high.It is proved that 65.8 % of respondent answers are aware and the remaining 44.2 % are not aware of the negative effects of the corruption. Besides,the school society also recognizes that the factor supporting the implementation of anti-corruption education in the school is very high, namely 93.4 %,the rest is only 6.6 % that does not support it. The implementation of anti –corruption curriculum in the high school Pacitan has been generally integratedin the daily life at school. However, the level as well as the intention is still quite low. It is proved from the texts of Islamic Education, Civics and othersubjects, there is no specific subject discussing the corruption.